2023
DOI: 10.21037/jtd-22-1528
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective medication in Duchenne muscular dystrophy: a single-centre cohort study

Abstract: Background: Duchenne muscular dystrophy (DMD) is a neuromuscular disorder characterised by progressive muscle wasting impacting mobility, ventilation and cardiac function. Associated neuromuscular cardiomyopathy remains a major cause of morbidity and mortality. We investigated the effects of cardioprotective medications [angiotensin-converting enzyme inhibitors (ACE-I), beta-blockers] on clinical outcomes in DMD patients.Methods: This was a retrospective cohort study (reference: 2021/12469) of DMD patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Overall, we found that these patients tended to be undertreated compared with other patients with systolic heart failure (see percentages under medication and LVEF at transition to adult medicine and at last visit in table 1 ) and considering current heart failure guidelines [ 24 ]. These figures are comparable to a recently published cohort study from another tertiary centre [ 25 ]. Among the 32 out of 67 patients in our study with LVEF <35%, an ACE-I was used in 25 out of the 32 (78%) at some point during follow-up with LVEF <35%.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, we found that these patients tended to be undertreated compared with other patients with systolic heart failure (see percentages under medication and LVEF at transition to adult medicine and at last visit in table 1 ) and considering current heart failure guidelines [ 24 ]. These figures are comparable to a recently published cohort study from another tertiary centre [ 25 ]. Among the 32 out of 67 patients in our study with LVEF <35%, an ACE-I was used in 25 out of the 32 (78%) at some point during follow-up with LVEF <35%.…”
Section: Discussionsupporting
confidence: 90%
“…the longer the ACE-I use, the longer the survival, but perhaps the longer ACE-I use simply reflects the early onset of systolic heart failure. In another recent cohort study, longer usage of heart failure drugs during follow-up was associated with a smaller decline of LVEF during follow-up, but the authors did not study survival [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we found that these patients tended to be undertreated compared with other patients with systolic heart failure (see percentages under medication and LVEF at transition to adult medicine and at last visit in table 1) and considering current heart failure guidelines [24]. These figures are comparable to a recently published cohort study from another tertiary centre [25]. Among the 32 out of 67 patients in our study with LVEF <35%, an ACE-I was used in 25 out of the 32 (78%) at some point during follow-up with LVEF <35%.…”
Section: Discussionsupporting
confidence: 80%